2018
DOI: 10.1016/j.scib.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and treatment of hypertension in China: impacts of 2017 American College of Cardiology/American Heart Association High Blood Pressure Guideline

Abstract: a b s t r a c tThe definition, recommended treatment thresholds and targets of hypertension have been updated in the recent 2017 American College of Cardiology/American Heart Association (ACC/AHA) Guideline for the Prevention, Detection, Evaluation and Management of High Blood Pressure in Adults. However, the impacts of this guideline on Chinese population are currently unknown. In this study, we aim to provide updated data in China using criteria from the updated guideline. A multistage, stratified sampling m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…3 and China among adults aged 45-75 years, respectively. Using longitudinal CHNS data, the present study protracted the previous prevalence of hypertension from several cross-sectional studies in China [6][7][8] and demonstrated an increasing secular trend of hypertension prevalence based on 2017 ACC/AHA guideline, which is different from the long-term trend among US adults. 16,17 In addition, we observed that the rate of increase in the prevalence of hypertension based on 2017 ACC/AHA guideline is significantly steeper than that estimated by the 2018 Chinese guideline (β = 1.00% per year versus β = 0.67% per year, P = 0.041).…”
Section: Discussionsupporting
confidence: 46%
“…3 and China among adults aged 45-75 years, respectively. Using longitudinal CHNS data, the present study protracted the previous prevalence of hypertension from several cross-sectional studies in China [6][7][8] and demonstrated an increasing secular trend of hypertension prevalence based on 2017 ACC/AHA guideline, which is different from the long-term trend among US adults. 16,17 In addition, we observed that the rate of increase in the prevalence of hypertension based on 2017 ACC/AHA guideline is significantly steeper than that estimated by the 2018 Chinese guideline (β = 1.00% per year versus β = 0.67% per year, P = 0.041).…”
Section: Discussionsupporting
confidence: 46%
“…“Expert consensus and Group Standard on body weight Management of overweight or obese population,” [6] 2010 revised edition of “Chinese guidelines for the Prevention and treatment of Hypertension,” [7] “The guidelines for the Prevention and treatment of Adult dyslipidemia,” [8] and “the Dietary guidelines for Chinese residents” [9] were used as the basis for the determination of overweight and obesity, hypertension, dyslipidemia, and lifestyle. Judging standard of bad life style: Physical activity was insufficient: daily work was mainly light activity, or moderate physical activity was <5 days per week, cumulative weekly activity time was <150 minutes; Smoking: it refers to those who smoke >1 cigarette a day on average and drink alcohol for >1 year; Drinking: men drink >25 g and females drink >15 g per day; Insufficient intake of cereal potato: <250 g of potato intake per day; Excessive intake of livestock and poultry meat: more than 75 g per day; Insufficient intake of fruit: <200 g of fresh fruit per day; Insufficient intake of vegetables: <300 g of fresh vegetables per day.…”
Section: Objects and Methodsmentioning
confidence: 99%
“…The impact of hypertension on NCDs has been recognized for more than 60 years. Evidence showed that when the SBP exceeded 115 mmHg, the incidences for stroke and coronary heart disease began to rise, regardless of the inconsistent criteria for hypertension [31][32][33].…”
Section: Discussionmentioning
confidence: 99%